Development and usability testing of a preliminary web-based application for the clinical implementation of blood flow restriction: a mixed methods pilot study - Wedig, Isaac J.; Petushek, Erich J.; Durocher, John J.; McDaniel, John; Elmer, Steven J. (Frontiers in Physiology, 2025)
IntroductionExercise with blood flow restriction (BFR) has gained popularity for use with a wide range of healthy and clinical populations. However, several factors including medical screening, selection of equipment, and determination of cuff pressure still pose barriers for implementation. Accordingly, this study aimed to develop and test a web-based application to guide practitioners in using BFR safely and effectively.MethodsFirst, we developed an application to assist with medical screening, selection of appropriate equipment, and determination of cuff pressures. Subsequently, we conducted preliminary usability testing of the application using a mixed methods approach. Licensed physical therapists (n = 5) with no prior experience with BFR used the application to implement BFR exercise in hypothetical patient scenarios. Afterward, perceived usability was assessed using the System Usability Scale (SUS) and semi-structured interviews analyzed through thematic analysis.ResultsAll task scenarios were successfully completed in an average time of 2.3 ± 1.2 min. A total of 11 errors occurred, including minor navigation issues (4), data input problems (2), and difficulty interpreting recommendations (5). The composite SUS score was 94 ± 5, ranking highly compared to industry standards. Interviews revealed that the application was efficient, boosted confidence in using BFR, and increased the perceived likelihood of incorporating BFR into clinical practice.DiscussionThese findings suggest that the web-based application has potential to serve as a valuable tool for overcoming barriers to BFR use, enhancing accessibility, and improving the safety and effectiveness of BFR implementation in clinical settings.